The Euro bloc, the Dollar bloc and the Yen bloc: how much monetary policy independence can exchange rate flexibility buy in an interdependent world? - Marcel Fratzscher (European Central Bank (ECB), 2002)
The paper analyses the trade-off between exchange rate flexibility and monetary policy autonomy. It tests empirically the 'Possible Duality' hypothesis, i.e. whether countries with more flexible currency regimes are indeed able to exert more monetary policy autonomy than those with less flexible ones, and whether moving towards exchange rate flexibility allows countries to gain monetary independence. The results for a set of open emerging markets and ERM countries show no systematic link between exchange rate flexibility and monetary independence. It is also found that the Fed is still the dominant force in world capital markets, although the importance of EU monetary policy decisions has been increasing and a Euro bloc has formed in Europe.
Keywords: F41; F31; E50; 330; error correction model; exchange rate regime; GARCH; international transmission; monetary policy